Implementasi Supervisi Kepala Sekolah dalam Meningkatkan Kinerja Guru Di Madrasah Ibtidaiyah (MI) Sirojul Athfal Pondok Rajeg Cibinong Bogor - Listi Wulandari; Yanti Hasbian Setiawati; Ahmad Riyadi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This research is based on the demands of the community's needs for quality and higher-quality education. Supervision is an important thing that needs to be done in an effort to improve the quality of education. This supervision is in the form of encouragement, guidance, and opportunities to grow teacher expertise in carrying out their professional duties. This study aims to identify and describe the implementation of school principal supervision in improving teacher performance. This research was conducted at MI Sirojul Athfal Pondok Rajeg Cibinong Bogor. This research is based on the boardman's theory of supervision. This study uses a qualitative descriptive method supported by data collection through interviews, observation, and documentation. The sources of informants in this research were the principal and two teachers. The results of this study indicate that the implementation of the supervision of the principal at MI Sirojul Athfal goes well every semester on a regular and scheduled basis. In stimulating teacher performance, the principal provides support, facilities, and appreciation for teachers. In coordinating teacher performance, the principal holds related coordination meetings, evaluates learning, conducts peer tutoring, and involves teachers in community activities. The school principal provides input, suggestions, and solutions related to difficulties faced by teachers, and in an effort to improve teacher performance, the principal provides motivation and optimizes facilities. Keywords : Principal Supervision, Teacher Performance